Stability analysis, agronomic performance, and grain quality of elite new plant type rice lines (Oryza sativa L.) developed for tropical lowland ecosystem - Aswidinnoor, Hajrial; Listiyanto, Risky; Rahim, Syaifullah; Holidin,; Setiyowati, Heny; Nindita, Anggi; Ritonga, Arya Widura; Marwiyah, Siti; Suwarno, Willy Bayuardi (Frontiers in Sustainable Food Systems, 2023)
Rice is a major world staple food crop, and therefore breeding improved varieties is of ultimate importance. Genotype-by-environment analyses are essential to understand the potential performance of the lines over environments. This study aimed to elucidate the stability, agronomic performance, and grain quality of elite new plant type (NPT) rice lines developed for tropical lowland areas. Elite NPT rice lines were evaluated in eight locations along with national varieties as checks. Combined analysis across environments and several stability analyses were performed. The results revealed the possibility of breeding high-yielding NPT rice varieties with different stability profiles, namely broad adaptation (IPB189-F-13-1-1 (G5), bi=0.91), suited for favorable environments (IPB187-F-37-1-2 (G1), bi=1.47), and adapted to marginal environments (IPB193-F-30-2-1 (G9), bi=0.54). G1 and G5 belonged to different groups of grain characteristics, each with low and high amylose content, respectively. The highest yielding line (IPB189-F-23-2-2 (G6), 8.68 ton ha -1 ) had an advantage of 19.39% over the highest yielding check, i.e., Inpari 32 (7.27 ton ha -1 ). This increase in yield was contributed by the success of breeding with a greater 1000-grain weight (11.91%) and number of filled grains per panicle (42.37%) than Inpari 32; meanwhile, the plant height also increased by 19 %. In addition, the rank correlations among three stability parameters, s 2 di, W 2 i, and σ 2 i were positive and highly significant. This study enlightens the prospect of breeding NPT rice varieties with different adaptations in tropical lowland areas.